2015
DOI: 10.1016/j.bbr.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic and serotonergic neurochemistry arising from intranasal inoculation with α-synuclein aggregates which incite parkinsonian-like symptoms

Abstract: Alpha-synuclein (α-syn) toxic aggregates delivered by the nasal vector have been shown to modify the neurochemistry of dopamine (DA) which is associated with parkinsonian-like motor symptoms. The aim was therefore to study the intranasal effects of α-syn oligomers, fibrils or their combination on the motor behavior of aged mice in relation to possible noradrenergic and serotonergic correlates. In vitro generated α-syn oligomers and fibrils were verified using atomic force microscopy and the thioflavin T bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…αSn monomer concentration is important for its aggregation, where a higher concentration aggregates faster. This is also visible in the table, where αSn incubation is done, either at low concentrations for a longer period (up to 7 days), or at higher concentrations for a shorter time (<24 hrs) . The different conditions result in a heterogeneous group of αSOs.…”
Section: Large Variety Of α‐Synuclein Oligomeric Speciesmentioning
confidence: 81%
See 1 more Smart Citation
“…αSn monomer concentration is important for its aggregation, where a higher concentration aggregates faster. This is also visible in the table, where αSn incubation is done, either at low concentrations for a longer period (up to 7 days), or at higher concentrations for a shorter time (<24 hrs) . The different conditions result in a heterogeneous group of αSOs.…”
Section: Large Variety Of α‐Synuclein Oligomeric Speciesmentioning
confidence: 81%
“…Despite the sparse evidence for αSO seeding ability, one study reported that αSOs, in contrast to fibrils, were able to spread pathology in vivo following injection in the olfactory bulb . In contrast, another group reported that αSOs were indeed able to spread pathology in vivo following injection in the brain, but fibril injection was more effective and also resulted in motor deficits, in contrast to αSOs ,…”
Section: α‐Synuclein Seeding and Spreadingmentioning
confidence: 99%
“…We analyzed levels of DA, NA, and 5-HT in the left and right striatum of all rats. To validate the 6-OHDA-induced lesion, the content of monoamines in these samples (nmol/g of tissue) was measured using HPLC with electrochemical detection, as described elsewhere [34] [35].…”
Section: Analysis Of Neurotransmittersmentioning
confidence: 99%
“…In fact, more recently many authors have investigated the effects of DA or L-Dopa intranasally applied [11][12][13][14][15][16][17]. Moreover, the intranasal administration has been used by different authors to test the prion-like spreading of pathological a-synuclein in the brain [18][19][20][21]. In particular, it has been reported that nasal administration of a-syn amyloidogenic species produce dopaminergic but also non-dopaminergic parkinsonian neurochemical alterations as well as behavioral deficits indicated by rigidity and reduced locomotor activity [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the intranasal administration has been used by different authors to test the prion-like spreading of pathological a-synuclein in the brain [18][19][20][21]. In particular, it has been reported that nasal administration of a-syn amyloidogenic species produce dopaminergic but also non-dopaminergic parkinsonian neurochemical alterations as well as behavioral deficits indicated by rigidity and reduced locomotor activity [18][19][20]. In this respect, it has been demonstrated that there is a final common pathway linking olfactory neuroepithelial receptor cells with axonal projections of the olfactory bulb and these networks are connected to centrifugal neuronal afferents from the substantia nigra dopamine nuclei [22].…”
Section: Introductionmentioning
confidence: 99%